Isu-isu Kritis dalam Pendidika "Lemahnya Kualitas Tes Ujian Akhir Sekolah Berstandar Nasional (UASBN) di Tingkat Sekolah Dasarâ€ - Eva Dwi Kumala Sari (Almarhalah | Jurnal Pendidikan Islam, 2017)
The writing of this paper is based on the low quality of basic education in Indonesia by looking at the results of the Indonesian version of TIMSS in 2006 (Puspendik, 2007) showing mathematical and linguistic achievements, with a standard of achieving 65% of questions answered correctly, there will only be less than 10% of sample students test that is able to achieve it. The writing of this paper aims to determine the quality of the national standard school final examination (UASBN) used, for primary school examinations. The approach used in writing this paper is a descriptive method, namely solving problems that arise and then analyzed based on alternative theories that can be considered as a way out of the problems encountered. The study population included parents and student responses to UASBN items. (1) Describe the learning weaknesses that are found in elementary schools based on information from UASBN; (2) Describe the map of cognitive weaknesses of elementary school students in the learning process and answer the UASBN